KEEFEKTIFAN MODEL PEMBELAJARAN THINK PAIR SHARE DENGAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI STATISTIKA KELAS VII - Rhohmat Atik Nurul Khasanah; Iswahyudi Joko Suprayitno; Eko Andy Purnomo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The problem in this research was students’ having difficulties in understandingstatistic data questions which served both in sentences and pictures format, which then caused them to having difficulties in reaching the correct conclusionfor said questions. Aside from that, students’ motivation and discipline inteaching learning process are relatively low. One way that could be used tosolve these problems were to apply Think Pair Share teaching learning modelwith contextual approach. This research aimed for understanding theeffectiveness of Think Pair Share teaching learning model with contextualapproach toward students’ mathematical communication skills on grade VIIstatistics material. This research was an experiment research, with every gradeVII students of SMP Muhammadiyah 3 Semarang academic year 2016/2017 asthe population.The samples in this reasearch were class VII F as experimentalclass, class VII C as control class, and class VII D as test class. The result ofthis research showed that the class in which Think Pair Share teaching learningmodel with contextual approach applied reach 93,33% classical passing mark;the influence of students’ motivations and disciplines toward their mathematicalcommunication skills were 77,5%; and the difference of mathematicalcommunication skills between experimental class and control class was 83,40 to55,54. According to those results, we can conclude that applying Think PairShare teaching learning model with contextual approach to improve students’mathematical communication skills in grade VII statistics material is effective.This teaching learning model can be used in other materials to improvestudents’ mathematical communication skills. Keywords: Think Pair Share, contextual, mathematical communication skills.